Laryngeal ultrasound and pediatric vocal fold nodules. (6th August 2016) - Ongkasuwan, Julina; Devore, Danielle; Hollas, Sarah; Jones, Jeremy; Tran, Brandon
Abstract : Objectives/Hypothesis: The term vocal fold nodules refers to bilateral thickening of the membranous folds with minimal impairment of the vibratory properties of the mucosa. Nodules are thought to be related to repetitive mechanical stress, associated with voice use patterns. Diagnosis is typically made in the office via either rigid or flexible laryngeal stroboscopy. Depending on the individual child, obtaining an optimal view of the larynx can be difficult if not impossible. Recent advances in high‐frequency ultrasonography allows for transcervical examination of laryngeal structures. The goal of this project was to determine if laryngeal ultrasound (LUS) can be used to identify vocal fold nodules in dysphonic children. Study Design: Prospective case‐control study in which the patient acted as his or her own control. Methods: Forty‐six pediatric patients were recruited for participation in this study; the mean age was 4.8 years. Twenty‐three did not have any vocal fold lesions and 23 had a diagnosis of vocal fold nodules on laryngeal stroboscopy. Recorded LUSs were reviewed by two pediatric radiologists who were blinded to the nodule status. Results: There was substantial inter‐rater agreement (κ = 0.70, 95% confidence interval [CI]: 0.50‐0.89) between the two radiologists regarding the presence of nodules. There was also substantial agreement (κ = 0.87, 95% CI: 0.72‐1) between LUS and laryngeal stroboscopy. Sensitivity of LUS was 100% (95% CI: 85%‐100%) and specificity was 87% (95% CI: 66%‐97%). Conclusions: LUS can be used to identify vocal fold nodules in children with substantial agreement with laryngeal stroboscopy. Level of Evidence: 3b Laryngoscope, 127:676–678, 2017